A Tentativie Accounting of the Forest Flora of North Cachar Hills and Barail Range - Dutt, A. K.; Dutta, T. K.; Gupta, K. K. (Indian Forester, 1974)
The forests of North Cachar Hilis and Barail Range of Assam were explored by the author in February, 1971 and a large number of interesting specimens were collected. The present paper covers Dicotyledones, Polypetalae, with 314 species (+ 1 spp & 2 vats) representing 218 genera and distributed over 77 families. The system of Bentham and Hooker with modifications. Made in conformity with modern concepts has been followed. The scientific names of the plant listed in the present work have been corrected as for as possible.